2015
DOI: 10.1111/jopr.12324
|View full text |Cite
|
Sign up to set email alerts
|

pH and Erosive Potential of Commonly Used Oral Moisturizers

Abstract: Patients with dry mouth are at increased risk for erosion and root caries. Oral moisturizing agents are often prescribed for patients with hyposalivation to be used as needed for symptomatic relief. This study shows that there is large variation in the pH values and erosive potential of commonly used oral moisturizing agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 14 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…Recent studies have concluded that there is a large variation in the pH values among the most common oral moisturizers on the market ( Table 1 ) and that there is a strong correlation between the pH values and the erosive potential of these products. 12 , 15 The data presented in this study show great variation in the composition and pH values among commercially available oral moisturizers. Several of the tested products contained citric acid or citric flavors, most likely to provide a pleasant taste.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Recent studies have concluded that there is a large variation in the pH values among the most common oral moisturizers on the market ( Table 1 ) and that there is a strong correlation between the pH values and the erosive potential of these products. 12 , 15 The data presented in this study show great variation in the composition and pH values among commercially available oral moisturizers. Several of the tested products contained citric acid or citric flavors, most likely to provide a pleasant taste.…”
mentioning
confidence: 74%
“…8 The critical pH of dentin was first reported by Hoppenbrouwers et al in 1987 at 6.7, 9 and it was confirmed 2 years later by Surmount et al 8 Several studies have reported the critical pH of dentin to be in a range of 6–6.9. 10 12 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pH of the foam mouthwash was 7.4 which is similar to Bioténe Oral Balance which also contains lactoperoxidase and has previously been shown to not cause enamel erosion. 24 The SEM images show that the biofilm was not uniformly developed over the surface but that the amount removed following a 5 s rinse with the foam mouthwash was greater than with saline. Increasing the exposure time to 30 s would most likely remove more of the formed biofilm as evidenced in the first part of the study.…”
Section: Discussionmentioning
confidence: 95%
“…The heating of an antifungal drug (fluconazole) has been shown to significantly increase its ability to inhibit biofilm formation by C. albicans [ 25 , 26 ]. Generally, the pH of a substance changes depending on the temperature, but the pH of commercially available oral moisturizers varies greatly depending on the type of product [ 27 ]. Therefore, the storage temperature and pH of an oral moisturizer might influence its antifungal effect.…”
Section: Introductionmentioning
confidence: 99%